2018
DOI: 10.1088/1361-6579/aaad5a
|View full text |Cite
|
Sign up to set email alerts
|

A microbeam grazing-incidence approach to L-shell x-ray fluorescence measurements of lead concentration in bone and soft tissue phantoms

Abstract: ObjectiveL-shell x-ray fluorescence (LXRF) is a non-invasive approach to lead (Pb) concentration measurements in the human bone. The first studies were published in the early 1980s. In the same period the K-shell x-ray fluorescence (KXRF) method using a Cd-109 radionuclide source was developed and later improved and refined. Lower sensitivity and calibration difficulties associated with the LXRF method led the KXRF to be the most adopted method for in vivo human bone Pb studies. In the present study a microbea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…The OGIP methodology employed in this study significantly reduced the total x-ray exposure and data acquisition times reported in our previous study [25]. In the previous approach, the precision of finding the OGIP was strongly dependent on the step size in the phantom positioning sequence.…”
Section: Discussionmentioning
confidence: 93%
See 4 more Smart Citations
“…The OGIP methodology employed in this study significantly reduced the total x-ray exposure and data acquisition times reported in our previous study [25]. In the previous approach, the precision of finding the OGIP was strongly dependent on the step size in the phantom positioning sequence.…”
Section: Discussionmentioning
confidence: 93%
“…In a commercial poP product, Pejović-Milić et al [33] measured a concentration of 4 mg Sr/g Ca. Hence, short-time (10 s) acquisition spectra were sufficient to determine the optimal bone phantom positions as in our previous study [25]. Sr K-edge and Pb L 3 -edge energies are relatively close at 13.0 and 16.1 keV, as provided in the first two columns of table 2.…”
Section: Methodsmentioning
confidence: 91%
See 3 more Smart Citations